The ANALYSIS OF FACTORS THAT AFFECT STOCK PRICES IN CONSUMER GOODS INDUSTRIAL SECTOR COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX (JII): ANALYSIS OF FACTORS THAT AFFECT STOCK PRICES IN CONSUMER GOODS INDUSTRIAL SECTOR COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX (JII) - Dhea Aulia Damayanti (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
This study aims to analyze the effect of Earning Per Share (EPS) and Dividend Payout Ratio (DPR) on share prices in the consumer goods industry sector companies listed in the Jakarta Islamic Index (JII). There are 4 companies that are the objects of research. The writing method used was a quantitative research method, with the type of data used was secondary data in the form of annual financial statement data and stock prices, obtained from the official website of the Stock Exchange Indonesia (IDX). Technical data analysis conducted of classic assumption test includes; normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, then hypothesis testing includes; multiple linear regression test, coefficient of determination test (